Consumer-orientated development of hybrid beef burger and sausage analogues - Neville, Michelle; Tarrega, Amparo; Hewson, Louise; Foster, Tim (Wiley, 2017)
Hybrid meat analogues, whereby a proportion of meat has been partially replaced by more sustainable protein sources, have been proposed to provide a means for more sustainable diets in the future. Consumer testing was conducted to determine consumer acceptability of different formulations of Hybrid beef burgers and pork sausages in comparison to both meat and meat free commercial products. Acceptability data was generated using the 9-point hedonic scale. Check-all-that-apply (CATA) questioning was used to determine the sensory attributes perceived in each product as well as information on the attributes of consumers’ ideal products. It was identified that Hybrid products were generally well liked among consumers and no significant differences in consumer acceptability (p < 0.05) was identified between Hybrid and full meat products whereas meat free products were found to be less accepted. However, hybrid sausages received higher acceptability scores (6.00 to 6.51) than Hybrid burgers (5.84 to 5.92) suggesting format may have a large impact on consumer acceptability of Hybrid products. Correspondence Analysis (CA) indicated that Hybrid products were grouped with meat products in their sensory attributes. Penalty analysis found that a ‘meaty flavour’ was the largest factor driving consumer acceptability in both burgers and sausages. Cluster analysis of consumer acceptability data identified key differences in overall acceptability between different consumer groups (consumers that only eat meat products and consumers who eat both meat and meat free). The Hybrid concept was found to bridge the acceptability gap between meat and meat free, however further product reformulation is required to optimise consumer acceptability.